O «mal de Loanda» ou o escorbuto revisitado - Morais, J. A. David de (2014)
The studies about “mal de Loanda” (scurvy) along the Portuguese history are scarce and brief. Therefore, the author addresses the national historiography on this issue, both in terms of its occurrence on the ships of the Portuguese “Descobertas,” and in the context of African slavery. After, the problem of scurvy is analyzed from the perspective of Anthropological Medicine.